Role of CD44 in tumor‐initiating cells of salivary gland pleomorphic adenoma: More than a surface biomarker. (29th January 2020) - Shen, Shukun; Lu, Hao; Liu, Limin; Wang, Yang; Zhang, Chenping; Yang, Wenjun; Xu, Wanlin
Abstract: CD44, a cell‐surface glycoprotein, functions as a receptor for hyaluronic acid. Our research group has previously shown that CD44 is a biomarker for the CD44 hi cells (tumor‐initiating cells; TICs) in murine salivary gland tumors. However, little is known concerning the biological roles of CD44 in the tumorigenesis of pleomorphic adenoma. The present study is aimed to investigate the effects of CD44 on the proliferation, invasive capability, and apoptosis of TICs in vitro, as well as the tumorigenicity of TICs in vivo. The results demonstrated that knockdown of CD44 attenuated the malignant phenotype of TICs. Furthermore, in vivo xenograft studies indicated that CD44 knockdown inhibited tumorigenesis of pleomorphic adenoma. In addition, neither the CD44 low cells nor the CD44‐modified CD44 low cells developed neo‐tumors, which indicated that overexpression of CD44 did not enable the CD44 low cells to be transformed into TICs. Taken together, these data demonstrate that CD44 not only acts as a biomarker, but also functions as a key player in the tumor‐initiating capacity of TICs. These results shed light on the pathogenesis of salivary gland tumors and provide a potential therapeutic target for treating pleomorphic adenoma.